Effect of Incorporation of De-Oiled Distillers Dried Grain with Solubles in the Concentrate Mixture on Growth Performance of Murrah Buffalo Calves - Pujitha, Tanguturi; Kumar, Mula Ravi; Kavitha, Pathakamuri; Venkata Seshaiah, Chappidi (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
This experiment was aimed to assess the impact of inclusion of de-oiled DDGS (dDDGS) as source of protein to replace cotton seed cake protein (CSC) in the concentrate mixture on growth, nutrient digestibility and cost economics. In a 90 days growth trial, 18 buffalo calves in the age range of 6-9 months old and 79-84 kg BW were randomly divided into three groups and allotted to one of the dietary treatments. In the experimental feeds CSC (on CP basis) was substituted with de-oiled DDGS at 0% (T1), 50% (T2) and 100% (T3) levels. The findings suggested that BW, ADG and FCR had significantly (p<0.01) increased in the T3 group compared to control group. Digestibilities of DM, CP, CF (p<0.01), OM and cellulose (p<0.05) were significantly increased in T3 group. The cost of feed/kg BW gain decreased by Rs. 35 in T3 and Rs. 15 in T2 group when compared to control group. DCP and TDN contents expressed either as intake (kg/d) or as % in diet consumed increased significantly (p<0.01). The DCP intake expressed as g/kg W0.75 was significantly (p<0.01) improved in T3 group. The DM, DCP and TDN intakes expressed as g/kg W0.75 and ME intake (M cal/kg W0.75) were similar among the treatments. It is concluded that de-oiled DDGS is an alternative to CSC for reduction of cost/kg live weight gain.